Endocranial morphology of Microchoerus erinaceus (Euprimates, Tarsiiformes) and early evolution of the Euprimates brain. Issue 1 (21st September 2015) - Ramdarshan, Anusha; Orliac, Maeva J.
ABSTRACT: Objectives: Innovations in brain structure and increase in brain size relative to body mass are key features of Primates evolutionary history. Surprisingly, the endocranial morphology of early Euprimates is still rather poorly known, and our understanding of early euprimate brain evolution (Eocene epoch) relies on a handful of specimens. Materials and Methods: In this article, we describe the endocranial cast of the tarsiiform Microchoerus erinaceus from the late Early Eocene of Perrière (Quercy fissure filling, France) based on a virtual reconstruction extracted from CT scan data of the endocranial cavity of the complete, undeformed specimen UM‐PRR1771. Results: The endocast of M. erinaceus shows the derived features observed in other Euprimates (e.g. sylvian fissure and temporal lobe), with limited neocortical folding, and a telencephalic flexure comparable to that of extant primates. Discussion: Comparison with the endocasts of other available late Eocene primates shows that they already exhibited a variety of brain morphologies, highlighting the complex history of the external features of the primate brain, as early as the Eocene. M. erinaceus was a fruit and gum eater considered as nocturnal based on its orbit size. However, its brain showed small olfactory bulbs—smaller than in the coeval diurnal taxa Adapis parisiensis— and a neocorticalization similar to folivorous taxa. These observations contrast with patterns observed in primates today where nocturnal taxa have larger olfactory bulbs than diurnal taxa, and call into question a direct correlation between frugivory and neocorticalization increase in primates. Am J Phys Anthropol 159:5–16, 2016. © 2015 Wiley Periodicals, Inc.